O corpo e os adereços : sepultamentos humanos e as especificidades dos adornos funerários - Silva, Jaciara Andrade (2013)
This research aims to analyze human burials through the Archaeothanatological methods. We focus on studying skeleton deposition in its graves and the adornments that were buried to them. Following the methodology aforementioned, our approach to gather details from human burials is realized intending to understand its original deposition (when it's originally kept) and other elements that we may link individuals to specific artifacts buried along the graves. Each skeleton characterization and singularities, such as pathologies and other alterations, must be considered in order to profile the deceased individuals. Referring to adornments, we analyze them according to geometrical characteristics and the material they are made of, so we may know this artifact “history” in order to establish a link to the individual who it was buried together. Knowing adornments’ historical trajectory may help us to make a chronological cut, specially to the period after Europeans groups arrival. The utilization of these two kind of products ensures that the natives contacted with the foreigns, so as the incorporation of European beads in burial adornments. The approach to human skeletons and the adornments in its graves intends to how these groups lived, including ceremonial burials, so these rituals show us that the attention given to the dead reflects, in many ways, the importance of the living.